2006
DOI: 10.1002/jnr.20785
|View full text |Cite
|
Sign up to set email alerts
|

S100B protects LAN‐5 neuroblastoma cells against Aβ amyloid‐induced neurotoxicity via RAGE engagement at low doses but increases Aβ amyloid neurotoxicity at high doses

Abstract: At the concentrations normally found in the brain extracellular space the glial-derived protein, S100B, protects neurons against neurotoxic agents by interacting with the receptor for advanced glycation end products (RAGE). It is known that at relatively high concentrations S100B is neurotoxic causing neuronal death via excessive stimulation of RAGE. S100B is detected within senile plaques in Alzheimer's disease, where its role is unknown. The present study was undertaken to evaluate a putative neuroprotective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 47 publications
(74 reference statements)
5
78
1
Order By: Relevance
“…Our in vitro experiments involving oxygen-glucose deprivation showed a dual effect of exogenous S100B on neuronal survival, being neuroprotective at low doses and neurotoxic at high doses. These results are in accordance with previous studies showing survival effects of S100B at relatively low concentrations against serum deprivation, glutamate, N-methyl-D-asparatate or amyloid-␤ peptide neurotoxicity (9,11,12). The requirement of RAGE for S100B protective effects was demonstrated in some of these paradigms (9,11).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our in vitro experiments involving oxygen-glucose deprivation showed a dual effect of exogenous S100B on neuronal survival, being neuroprotective at low doses and neurotoxic at high doses. These results are in accordance with previous studies showing survival effects of S100B at relatively low concentrations against serum deprivation, glutamate, N-methyl-D-asparatate or amyloid-␤ peptide neurotoxicity (9,11,12). The requirement of RAGE for S100B protective effects was demonstrated in some of these paradigms (9,11).…”
Section: Discussionsupporting
confidence: 92%
“…In vitro studies using primary neurons or neuroblastoma cells showed that stimulation of RAGE by low levels of S100B leads to neurite outgrowth, and activation of pro-survival pathways during stress conditions like trophic factor deprivation, glutamate, N-methyl-D-aspartate, or amyloid-␤ toxicity (9 -12). On the other hand, treatment of primary neurons, astrocytes, or microglia with relatively high doses of S100B leads to oxidative stress, NF-B activation, expression of proinflammatory mediators, and cytotoxicity (9,11,13,14). Little is…”
mentioning
confidence: 99%
“…Although S100B levels increase with normal aging [42,43], hippocampal and temporal lobe levels of S100B are significantly elevated in AD cases [26,44,45]. At micromolar extracellular concentrations, S100B can act as a cytokine, causing apoptosis and the production of reactive oxygen species (reviewed in [46,47]). Like A␤, S100B is a ligand for the receptor for advanced glycation end products (RAGE) which when activated can lead to increases in several AD-related signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Important role in pathogenesis of AD and chronic complications of DM play carbohydrate-derived advanced glycation end-products (AGEs) [43]. Post-mortem analyzed samples of AD with diabetes compared to AD without diabetes or non-demented controls have shown their significant increase [44]. RAGE is specific cell surface receptor for amyloid β and it results with easier neuronal damage [45,46].…”
Section: Role Of Insulin In Overall Degradational Process In Pathogenmentioning
confidence: 99%